Enhancing Aviation English for LTELS: Integrated ELD challenges and scenario-based innovations - Laila Rochmawati; Fatmawati Fatmawati (University of Muhammadiyah Malang, 2025)
This qualitative case study investigates how Aviation Englishinstructors at Politeknik Penerbangan Surabaya, Indonesia,integrate English Language Development (ELD) strategies intocontent teaching to support Aviation English Learners (AELs)with prolonged English instruction challenges in developinglanguage, literacy, and intercultural competence. Grounded inVygotsky’s Zone of Proximal Development, the study employssemi-structured interviews with four instructors and twoadministrators, supplemented by document analysis ofcurricula, lesson plans, and institutional policies, to examineinstructional practices and systemic barriers. Findings revealpersistent challenges in distinguishing AELs with extendedlearning needs from other learners and implementingmandated integrated ELD strategies, underscoring tensionsbetween integrated and designated ELD models. Instructorshighlight fostering academic optimism, high expectations, andadvanced literacy tasks, such as scenario-based simulations androle-plays, to promote productive struggle, significantlyenhancing student engagement and learning outcomes.Robust institutional support—through clear policies, targetedprofessional development, and aviation-specific curricula—iscritical for effective ELD implementation. The study advocatesfor authentic aviation communication tasks and interculturaltraining to elevate AELs’ English proficiency and interculturalskills, aligning with International Civil Aviation Organization(ICAO) standards for safety-critical communication. Thesefindings offer actionable pedagogical and administrativestrategies to enhance AEL outcomes in vocational education,addressing gaps in Indonesia’s aviation training andcontributing to safer, more effective global aviationcommunication.